Analysis of the Effectiveness of 20% Human Albumin Therapy Compared to 25% Human Albumin in Postoperative Digestive Surgery Patients With a Diagnosis of Hypoalbumin in the Intensive Care Room - Witha, Nikenly Fajar; Sriwahyuni, Fatma; Nasif, Hansen (Poltekkes Kemenkes Riau, 2024)
Hypoalbuminemia is generally identified in patients undergoing preoperative care, the recovery phase after surgery, and those in the healing process. At DR. M. Djamil General Hospital, the therapy to improve albumin levels in patients receiving intensive postoperative care involves using 20% human albumin and 25% human albumin. This study aims to evaluate and compare the effectiveness of 20% and 25% human albumin in increasing albumin levels in postoperative hypoalbuminemia patients at the institution. Data collection for this research was conducted retrospectively with a cross-sectional approach, where data were analyzed to determine how the increase in albumin levels after the administration of 20% or 25% human albumin affected clinical outcomes in patients. Findings from the proportionality testing in the subject characteristics involved in the research showed no disparity in the proportion of patient characteristics between the group receiving 20% human albumin (n=27) and the group receiving 25% human albumin (n=33) (p>0.05). Furthermore, the comparative mean analysis indicated a statistically significant difference in the levels of hypoalbuminemia before and after albumin infusion therapy in each group (p<0.05). The average increase in hypoalbuminemia in the group using 20% human albumin was recorded at 0.46 g/dL, while in the group with 25% human albumin, the increase reached 0.66 g/dL. Statistical analysis of the mean difference showed a statistically significant average increase in albumin concentration among the studied groups, with a p-value of less than 0.05. In this context, 25% of human albumin contributed to a significantly higher average increase in albumin concentration. Given the significant cost difference between 20% and 25% human albumin, it is recommended to use 20% human albumin for patients with albumin levels above 2.1 g/dL. Meanwhile, for patients with albumin levels below 2.1 g/dL, it is more appropriate to use 25% human albumin.